2010
DOI: 10.3109/14647273.2010.504805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin taken in the ‘fresh’in vitrofertilization/intracytoplasmic sperm injection cycle upon subsequent frozen embryo replacement in women with polycystic ovary syndrome

Abstract: Women with PCOS who take metformin during IVF/ICSI may have a higher LBR in subsequent FERC, especially in those who have elective cryopreservation for OHSS risk. The findings of this study are limited by its retrospective design and small sample size and require confirmation in an adequately powered prospective randomized controlled trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 56 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Despite widespread and continued use, the efficacy of metformin as a treatment for PCOS remains unproven and controversial. Metformin has been shown by some investigators to result in weight loss, normalization of menstrual cycles, and an improvement of conception rates following therapies such as ovulation induction and controlled ovarian hyperstimulation prior to in vitro fertilization (IVF) [ 16 - 19 ]. In contrast, other studies have demonstrated that metformin does not offer any clinical benefit [ 20 - 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite widespread and continued use, the efficacy of metformin as a treatment for PCOS remains unproven and controversial. Metformin has been shown by some investigators to result in weight loss, normalization of menstrual cycles, and an improvement of conception rates following therapies such as ovulation induction and controlled ovarian hyperstimulation prior to in vitro fertilization (IVF) [ 16 - 19 ]. In contrast, other studies have demonstrated that metformin does not offer any clinical benefit [ 20 - 22 ].…”
Section: Introductionmentioning
confidence: 99%